Non-Destructive Evaluation of Green Ceramic Body Density by Ultrasonic Technique - Kulokas, M.; Kazys, R.; Mazeika, L. (Elektronika ir Elektrotechnika, 2011)
Laboratory measurements of spatial density distribution in green ceramic tiles were implemented using ultrasonic contact coupling measurement method. The main objective of these measurements is to measure spatial density distribution in pressed green ceramic tiles. Measurements of longitudinal ultrasonic wave propagation velocity were carried out using pulse and correlation methods and the tile density values were calculated. Evaluation of the measurement method, estimation of uncertainty of measurements and analysis of further improvements purposed to adapt it for on-line measurements in a production process were carried out. Ill. 7, bibl. 16, tabl. 1 (in English; abstracts in English and Lithuanian). http://dx.doi.org/10.5755/j01.eee.111.5.360